Garantismo tributário - Scherer, Tiago (2025)
We start from values that animate our entire constitutional system and permeate the infra constitutional order. Fraternity and justice are the foundations of constitutionalism in our time, in which the fundamental rights to a dignified life, equality, freedom, property, and security are imbued with countless specific figures that specialize in other fundamental rights. We defend the idea that these constitutional rights must be guaranteed in order to be effective, and even to exist, because without guarantees they would be nothing more than words embellishing the normative text. If the legal-constitutional system needs to be stable, permanent, and immune to distortion, it needs guarantees. Hence, especially in tax matters, those fundamental rights find guarantees that stem from the very structure of Tax Law, which serves to guarantee the funding of goods that are indispensable to the free, just, fraternal, and supportive society that the Constitution idealizes. This Tax Law ceases to be a simple collection tool and becomes a mechanism for achieving solidarity, in which everyone is treated equally, there is mutual aid, and the common good prevails over selfishness. This Tax Law—a Guarantee-Based Tax Law— also respects the fundamental rights of taxpayers, in addition to reflecting mechanisms of social solidarity. Within it, there are other guarantees for taxpayers. In particular, the guarantee that taxpayers will not be arbitrarily taxed, but only through strict legality. The guarantee that the minimum necessary for a dignified life will not be subject to taxation. The guarantee that society will not pour resources into the State beyond what it – society – depends on in terms of services instrumental to the realization of the fundamental individual and collective rights contained in the Rule of Law. Guarantee that taxation will respect the ability to pay, but will not go so far as to become confiscatory. Guarantee that tax law does not cause unfair damage to taxpayers; taxation follows legal and instrumental parameters that are not used to inflict harm or damage beyond the transfer to the tax authorities of legally established and collected taxes. Instrumental guarantees that condition the validity of tax collection, since taxpayers, within a state governed by law, are not subject to the discretion of political power. Guarantee that society itself, through the rule of law, will have access to these resources, which are already truly public, even if not paid to the tax authorities. Guarantee that the State will have instruments for the collection of these resources. Guarantee that the collection of defaults will be effective, under penalty of ultimately undermining the ideals of justice and fraternity. Hence, this investigation recovers the origins and foundations of Tax Law to analyze them from the perspective of the theory of legal guarantees, proposing, at this intersection, the construction of ten tax guarantee theses, which support both the legitimate expectations of taxpayers and the community in the realization of fundamental rights and the construction of a freer, fairer, and more supportive society.